STUDY OF THE POSSIBILITY OF INCREASING THE ACCURACY OF THE ROBOT GRIPPING DEVICE DUE TO THE COMPENSATING LINK OF THE CLAMPING LEVER - HODUNKO, MAKSYM; MAZHARA, VITALII; KYSLUN, OLEG; SHCHERBINA, VOLODYMYR; PYSANKA, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Modern machine-building production involves the use of advanced technologies, constant improvement of equipment and technological processes of manufacturing parts. Considerable attention in this matter is paid to the automation of production processes. In flexible production, one of the main elements is industrial robots that serve the main technological equipment. One of the main tasks of high-quality and efficient performance of operations by a robot is its positioning accuracy, which is characterized by the minimum permissible error of reaching the position of the gripping device. In addition, there is a problem of displacement of the axis of the part in the gripping device when capturing parts of different diameters. This can be manifested with a significant change in the diameter of the part before and after processing, or with a change in the standard size of products. Therefore, it is urgent to solve the issue of the accuracy of the clamping of parts by the robot through constructive improvements or theoretical calculations. Features of the work of industrial robots and their gripping devices require high requirements for executive mechanisms. When choosing or designing gripping devices, it is necessary to take into account their ability to work with different parts, as well as the fact that they are placed on the final link of the robot arm, which during its work performs multi-vector spatial movements with high speeds and accelerations. All these factors affect the accuracy of the grip. Therefore, research is being conducted with the aim of finding ways to reduce the errors of capturing parts and improve the functionality of the robot locally, by changing the length of the clamping levers. Therefore, the error of displacement of the part in the gripping device occurs when the part is clamped with a diameter different from the nominal one. In some cases, such an error can be more than 10 mm, which is not acceptable when the robot is servicing the main technological equipment, or when performing assembly operations. But the amount of error can be reduced to an acceptable value, and even reduced to "0", using the proposed method, or by reprogramming the trajectory of the movement of the industrial robot to compensate for the positioning accuracy by the amount of error that occurs when the part is clamped.
Keywords: gripping devices; industrial works; compensating link; part displacement error